A study of the economic impact of central bank digital currency under global competition. Issue 1 (2nd January 2021) - Tong, Wu; Jiayou, Chen
ABSTRACT: From both theoretical and practical perspectives, we examine the global development and competition of digital currencies, and investigate the design of China's central bank digital currency (CBDC). Moreover, on the basis of correcting shortcomings in the existing literature, we undertake a quantitative analysis of the economic impact of the issuance of DC/EP based on a four-sector DSGE model. The results demonstrate that the substitution effect of DC/EP on bank deposits is limited, while the unit impact can enhance the economic growth rate by 0.15% and the overall economic effect is positive, at the same time it reduces the leverage ratio to a certain degree, which is conducive to reducing systemic financial risk. Therefore, we contend that China should accelerate the research and development of DC/EP and launch pilot schemes to promote DC/EP. Moreover, China should actively participate in the drafting of international regulations for digital currencies, selectively liberalize the jurisdiction of overseas nodes, jointly establish an integrated digital infrastructure for future generations.